Evaluation of Quality of Life of Parents and Growth Parameters of their Infants with Cleft Lip and Cleft Palate before and after Primary Surgery: An Observational Study - Nupur Saha; Shabnam Zahir; Siddhartha Chatterjee; Arnab Santra; Mainak Das (Journal of Clinical and Diagnostic Research, 2024)
Introduction: Cleft Lip (CL) and Cleft Palate (CP) are associated with several complications that have a significant negative impact on the Quality of Life (QoL) of affected children and caregivers. Compared to their healthy counterparts, children with these conditions experience feeding difficulties, cosmetic abnormalities, and, most importantly, diminished physical and cognitive growth, especially during the first year of their lives. Aim: To evaluate the growth parameters in CL and/or CP infants and the QoL of parents with a CL and/or CP child before and after primary surgery. Materials and Methods: For this observational study, data was collected longitudinally from the same set of Cleft lip and cleft palate (CL/CP)/CL&CP infants and their parents before and after the primary surgery. The study was conducted at the Department of Paediatric and Preventive Dentistry, Guru Nanak Institute of Dental Sciences and Research, West Bengal, ABMSS Kolkata Comprehensive Cleft Care Centre, West Bengal, and IMA Vaccination Centre Barasat, West Bengal, India, from December 2020 to May 2022. In this study, 66 children and 64 parents were included in each study and control group. Growth parameters {weight, length, Head Circumference (HC)} were measured using a weight analogue machine, infantometer, and HC measuring tape, and compared with those of healthy infants. The QoL of parents with CL and/or CP infants was quantified using a questionnaire form of “Revised Impact on Family Scale (RIOFS)” filled out by parents before and after six months of primary surgery and compared with the QoL of same-age healthy infants. The responses to the RIOFS questionnaire were scored according to recommended guidelines. The Statistical Package for Social Sciences (SPSS) Statistics 23.0 was used for data analysis. Results: Among the study groups, statistically significant differences in mean height, weight, and HC were observed between the groups of all infants with CL, CP, and CL with CP before and after the primary surgery (p<0.001). The QoL of parents from the study group improved post-surgery. The difference in mean RIOFS score between study Group-3 and study Group-4 after the primary surgery was statistically significant (p<0.001). Conclusion: The growth of CL and/or CP infants and the QoL of their caregivers are compromised compared to healthy infants. After primary surgery, the growth of CL and/or CP infants and the QoL of their parents partially improved.